Role of zinc enriched manures in enhancing yield and quality of maize (Zea mays) grown in zinc deficient calcareous soil - A, NAVEENKUMAR; PANDIAN, SARAVANA; DASH, AMIT K; RAZA, MD BASIT; HASANAIN, MOHAMMAD; SINGH, RAJIV KUMAR; M, LAXMANNARAYAN; TRIPATHY, SALONI (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2020–21 and 2021–22 at Agricultural College and Research Institute, Tamil Nadu to investigate the influence of various Zn sources [inorganic (ZnSO4 and Zn-EDTA), enriched organic manure (vermicompost + ZnSO4 and farm yard manure (FYM) + ZnSO4), and Zn solubilizing bacteria (ZSB)) (with and without ZnSO4)] on maize (Zea mays L.) growth and Zn accumulation in grain. The experiment was laid out in a randomized block design (RBD) with three replications taking maize hybrid variety i.e. Monsanto Dekalb as a test crop. Simultaneously, an incubation study with similar Zn sources was run to study the Zn release patterns for 10-weeks. The incubation experiment showed the total DTPA extractable Zn release over 10-weeks was significantly higher in ZnSO4 enriched vermicompost (ER–I) (94.5 mg/kg) than in the other Zn sources. The use of vermicompost enriched with ZnSO4, in combination with the recommended dose of fertilizers (RDF), noticeably increased grain yield to the tune of 8264 kg/ha when compared to other treatments. Additionally, this treatment significantly boosted Zn accumulation in grains and enhanced Zn availability in the soil, which surpassed all other treatments. Consequently, these findings underscore the pivotal role of Zn enriched vermicompost in facilitating Zn bio-fortification in maize crops grown in Zn deficient calcareous soil.